ANALISIS PENGARUH PERSEPSI RISIKO, KEMUDAHAN DAN MANFAAT TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE: STUDI KASUS PADA KONSUMEN BARANG FASHION DI FACEBOOK - Yunita Fitri Wahyuningtyas; Dyah Ayu Widiastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
The purpose of this research is to examine perceived risk, perceived ease to use, perceived benefit on buying decision online. Using internet to shopping online will give customers more benefit. In this research, data were obtained using a structured questionnaireon five point Likert Scale. An analytical process (validity, reliability and regression analysis) was performed to obtain 100 questionnaire. The Findings reveal that customer perceived risk, perceived ease of use and perceived benefit have significant and postitive effect on buying decision online. Consumer choose facebook as media shopping online because safety online transaction, consumer can access facebook without any fear of losing money. Facebook is easy to access for everyone with internet. Shopping activity will be more fun if can be accessed anytime and anywhere without any obstacles.